2017
DOI: 10.1097/jpa.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Physician Assistant Student Training for the Inpatient Setting

Abstract: Identifying the most essential content can facilitate curriculum development. Hospitalists have a knowledge gap about the training of PA students. The inpatient medicine rotation was rated positively, but survey responses suggested that a formal curriculum could have a positive effect and would be well received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…One study found that physician hospitalists have a poor understanding of the training PAs undergo and would favor a standardized curriculum for PA hospitalists. 25 Another study compared all PA postgraduate training programs in emergency medicine; 19 it also described a small number of relatively young programs with variable curricula and a need for standardization. Yet another paper 10 surveyed postgraduate PA programs across all specialties; however, that study only captured two hospital medicine programs, and it was not focused on several key areas studied in this paper-such as the program rationale, curricular elements, and assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that physician hospitalists have a poor understanding of the training PAs undergo and would favor a standardized curriculum for PA hospitalists. 25 Another study compared all PA postgraduate training programs in emergency medicine; 19 it also described a small number of relatively young programs with variable curricula and a need for standardization. Yet another paper 10 surveyed postgraduate PA programs across all specialties; however, that study only captured two hospital medicine programs, and it was not focused on several key areas studied in this paper-such as the program rationale, curricular elements, and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several publications detailing successful individual APP fellowships in medical subspecialties, 22 psychiatry, 23 and surgical specialties, 24 all of which describe the benefits to the institution. One study found that physician hospitalists have a poor understanding of the training PAs undergo and would favor a standardized curriculum for PA hospitalists 25 . Another study compared all PA postgraduate training programs in emergency medicine; 19 it also described a small number of relatively young programs with variable curricula and a need for standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that APPs are interested in formal postgraduate hospital medicine training, even if it means having a lower stipend during the first year after graduating from their NP or PA program. 9,15,18 The growing need for hospitalists, driven by residency workhour reform, increased age and complexity of patients, and the need to improve the quality of inpatient care while simultaneously reducing waste, has contributed to the increasing utilization of and need for highly qualified APPs in hospital medicine. 11,19,20 We established a fellowship to train APPs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Hospital medicine is the fastest growing medical field in the United States, and approximately 83% of hospitalist groups around the country utilize APPs; however, the demand for hospitalists continues to exceed the supply, and this has led to increased utilization of APPs in hospital medicine. [5][6][7][8][9][10] APPs receive very limited inpatient training and there is wide variation in their clinical abilities after graduation. 11 This is an issue that has become exacerbated in recent years by a change in the training process for PAs.…”
mentioning
confidence: 99%